Images and empires : visuality in colonial and postcolonial Africa - Landau, Paul Stuart, 1962-; Kaspin, Deborah D., 1953- (University of California Press, 2002)
This volume considers the meaning and power of images in African history and culture. It assembles a wide-ranging collection of essays dealing with specific visual forms, including monuments cinema, cartoons, domestic and professional photography, body art, world fairs, and museum exhibits.